A novel fiber Bragg grating system for eye tracking - Sharath Umesh; Shweta Pant; Srivani Padma; Sumitash Jana; Varsha Vasudevan; Aditya Murthy; Sundarrajan Asokan (Journal of Advanced Research, 2019)
Eye movement evaluation is vital for diagnosis of various ophthalmological and neurological disorders. The present study proposes a novel, noninvasive, wearable device to acquire the eye movement based on a Fiber Bragg Grating (FBG) Sensor. The proposed Fiber Bragg Grating Eye Tracker (FBGET) can capture the displacement of the eyeball during its movements in the form of strain variations on a cantilever. The muscular displacement generated by the eyeball over the lower eyelid, by its swiveling action while moving the gaze on a target object, is converted into strain variations on a cantilever. The developed FBGET is investigated for dynamic tracking of the eye-gaze movement for various actions of the eye such as fixations, saccades and main sequence. This approach was validated by recording the eye movement using the developed FBGET as well as conventional camera-based eye tracker methodology simultaneously. The experimental results demonstrate the feasibility and the real-time applicability of the proposed FBGET as an eye tracking device. In conclusion, the present study illustrates a novel methodology involving displacement of lower eyelid for eye tracking application along with the employment of FBG sensors to carry out the same. The proposed FBGET can be utilized in both clinical and hospital environment for diagnostic purposes owing to its advantages of wear-ability and ease of implementation making it a point of care device. Keywords: Fiber Bragg grating sensor, Eye tracker, Eye muscular movement detection